Correlation between DNA methylation and gene expression in the brains of patients with bipolar disorder and schizophrenia. (22nd September 2014) - Chen, Chao; Zhang, Chunling; Cheng, Lijun; Reilly, James L; Bishop, Jeffrey R; Sweeney, John A; Chen, Hua‐Yun; Gershon, Elliot S; Liu, Chunyu
<x xml:space="preserve">Abstract</x> Objectives Aberrant DNA methylation and gene expression have been reported in postmortem brain tissues of psychotic patients, but until now there has been no systematic evaluation of synergistic changes in methylation and expression on a genome‐wide scale in brain tissue. Methods In this study, genome‐wide methylation and expression analyses were performed on cerebellum samples from 39 patients with schizophrenia, 36 patients with bipolar disorder, and 43 unaffected controls, to screen for a correlation between gene expression and CpG methylation. Results Out of 71, 753 CpG gene pairs (CGPs) tested across the genome, 204 were found to significantly correlate with gene expression after correction for multiple testing [p < 0.05, false discovery rate (FDR) q < 0.05]. The correlated CGPs were tested for disease‐associated expression and methylation by comparing psychotic patients with bipolar disorder and schizophrenia to healthy controls. Four of the identified CGPs were found to significantly correlate with the differential expression and methylation of genes encoding phosphoinositide‐3‐kinase, regulatory subunit 1 (PIK3R1), butyrophilin, subfamily 3, member A3 (BTN3A3), nescient helix‐loop‐helix 1 (NHLH1), and solute carrier family 16, member 7 (SLC16A7) in psychotic patients (p < 0.05, FDR q < 0.2). Additional expression and methylation datasets were used to validate the relationship between DNA methylation, gene expression, and neuropsychiatric diseases. Conclusions These results suggest that the identified differentially expressed genes with an aberrant methylation pattern may represent novel candidate factors in the etiology and pathology of neuropsychiatric disorders.